Vegetable consumption linked to decreased visceral and liver fat and improved insulin resistance in overweight Latino youth - Cook, Lauren T. (2014)
There is limited data on the impact of vegetable consumption on adiposity and metabolic health, specifically non-starchy vegetables (NSV) and vegetables that are dark green and deep orange/yellow (also known as nutrient-rich vegetables, NRV). This study examines the relationship between vegetable intake and adiposity, liver fat and insulin dynamics in overweight Latino youth. This cross-sectional study of 175 overweight (≥85(th) percentile BMI) Latino youth (8–18 years), with data collected 2006–2011, included the following: dietary intake via multiple 24-h recalls, total body fat via dual-energy x-ray absorptiometry, adipose tissue distribution and liver fat via magnetic resonance imaging, and insulin dynamics via frequently-sampled intravenous glucose tolerance test. Linear regression and analysis of covariance were used for analysis, with the following a priori covariates: age, sex, energy intake and total body fat. Participants who consumed the most NSV (mean intake = 1.7±1.0 servings/d) compared to the least (mean intake = 0.1±0.1 servings/d) had 44% less liver fat (10.0±8.5 vs. 5.6±8.7%, p=0.01). NRV intake was positively correlated with insulin sensitivity (SI, r=0.19, p=0.03). Consumers of NRV (mean intake = 0.3±0.4 servings/day, n=107), compared to non-consumers (n=68), had 31% increased SI (1.6±1.6 vs. 2.1±1.3 × 10(−4)·min(−1)·μU(−1)·mL(−1), p=0.03) and 17% less visceral adipose tissue (2.3±0.9 vs. 1.9±0.7 L, p=0.01). In conclusion, consumption of specific vegetable types by overweight Latino youth is associated with positive metabolic outcomes, including reduced visceral and liver fat and risk factors for type 2 diabetes, even when consumed in small quantities. These may be relevant targets for interventions.